Risk of Musculo-skeletal Disorders and the Development of Ergonomics Furniture for Primary School Children in Malaysia - Mohd Ali, Nurul Asyiqin (2010)
Musculoskeletal problems (MSD) among children are increasing worldwide from year to year. The school environment had been identified as one of the contributing factors in the increase of MSD complaints among children. The 2 main objectives of this study are: first, to determine the prevalence and risk factors of MSD among Malaysian primary school children; and second, to develope and evaluate new ergonomics furniture for primary schools in Malaysia. A cross-sectional study was carried out in 10 randomly selected primary schools from 4 regions in Peninsular Malaysia, with a total of 843 children participating in the study. A translated Nordic Questionnaire (TNQ) was used to determine the prevalence of MSD (life time complaints as well as complaints within 7 days of the interview). The schoolbags were weighed to determine the average weight carried by the school children. The ergonomics hazard and MSD risk factors were determined using Logistic Regression analysis and ergonomics Hazard Identification, Risk Assessment and Risk Control (HIRARC). From the risks identified, ergonomics furniture were designed with the color and material preferences as chosen by the children through a simplified questionaire. Anthropometric data was collected using a Martyn’s type anthropometer and a customized chair to determine the specifications of the furniture based on the anthropometry of level 1 (standard 1 to standard 3) and level 2 (standard 4 to standard 6) children. Using all the important information, several sketches were produced and only one final design was selected. Two-dimensional (2D) and 3-dimensional (3D) mock-ups were produced based on the selected sketches. The specifications of the furniture were finally intergrated with the anthropometric data for the final design prior to prototype fabrication . Finally, Rapid Upper Limb Assessment modelling analysis was done using CATIA® software to evaluate the effectiveness of the proposed prototypes. From the total respondents, 52% were females, most of them Malay (92%). The results showed that the overall prevalence of MSD (life time) was very high (66.5% for level 1 and 73% for level 2). From the assessment, the study revealed that 4 ergonomics parameters were found to be hazardous to school children, namely: 1) un-ergonomically designed furniture; 2) awkward posture; 3) prolong sitting; and 4) excessive loading. Among the children’s activities, classroom learning indicated the highest risk level of 15 (high risk) compared to others. Binary Logistic Regression analysis shows a significant relationship for NP with relative bag weight (X2=4.015, p<0.05, R2=0.084), EP with relative bag weight (X2=7.667, p<0.05, R2=0.585), and KLP with existing furniture (X2=4.934, p<0.05, R2= 0.23), among level 2 children. Among level 1 children, the results showed a significant relationship between EP and relative bag weight (X2=5.740, p<0.05, R2=0.177), UBP with existing furniture (X2=5.265, p<0.05, R2=0.377), THP with the trolley-type bag (X2=15.348, p<0.05, R2=0.393), KLP with the trolley-type bag (X2=8.278, p<0.05, R2=0.112) and SP with existing furniture (X2=9.577, p<0.001) and the trolley-type schoolbag (X2=6.343, p<0.05). The existing furniture contributed 14.1% to SP complaints while the trolley-type schoolbag contribute only 7.4%, with the combination of both factors contributing 21.5% (X2=15.921, p<0.05) to the dependent variable for Level 1 children. A majority of the school children (76%) preferred light colors to be used as furniture colors and 6 anthropometric parameter had been used in determining the dimensions of the new furniture. Using all the information, 2 primary school furniture prototypes had been developed. The RULA analysis showed the reduction of a grand score of 4 for the current furniture to 2 for the newly-proposed furniture design (levels 1 and 2). In conclusion, this study proposes a new design of school furniture, with the combination of medical science research and industrial design processes to promote safety and health among Malaysian school children. Keywords: Primary school children, MSD, HIRARC, Anthropometrics data, Furniture Development, RULA